Analisis Spasial Daerah Rawan Kecelakaan Lalu Lintas di Kota Kupang dengan Quantum GIS - Baba, Yanuarius Gennaro Ola; Seran, Engelbertha Noviani Bria (CV. Gio Architect, 2025)
Transportation in kupang city has a crucial role in the movement of people and goods using public transportation services. Salasatu services kupang city public transportation that is commonly used is (bemo). The number of accidents in kupang city is still high, based on data from bps (central statistics agency) east nusa tenggara province, over the last 4 years there have been 1,515 minor injuries, 292 serious injuries, and 157 who died. So, it is necessary to know by the people about the location of areas that are very prone to accidents. And it is expected to be able to be reduced, after knowing the vulnerable area. With the analysis method of traffic accident-prone areas, accident-prone areas (blacksite) or accident-prone areas (blackspot) can be known. Calculation in the type of collector road based on the calculation of the method of accident-prone areas known areas or areas are very vulnerable, vulnerable & quite vulnerable and made a map with the application (qgis).